Tafsir Era Sahabat: Mengenal Tafsir Ibnu Abbas - Nisa Azizatul; Aida Andryanto; Putri Adinda Yulia Handayani; Andini Dwi Andani (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
The large number of various interpretive books that have appeared today cannot be separated from historical events in the past. There are many schools or schools in the development of the science of interpretation with the aim of studying the history of the dynamics of the development of interpretation. The focus of the study is on ways of thinking, schools, patterns and tendencies that exist in interpretive products. Each interpretive product in each time period has different characteristics from one another. After the death of the Prophet Muhammad saw. The process of interpreting the Koran was continued by the companions of the Prophet. One of them was a very prominent friend of Ibn Abbas, he received the title Tarjuman al-Qur'an which is considered to be the foundation of the science of interpretation. There are several factors why Ibnu Abbas' friend is very prominent in the field of interpretation compared to other friends, including: Ibnu Abbas' intensity in taking knowledge from other friends, Ibnu Abbas' strength and sharpness in ijtihad, and being very serious in pursuing the interpretation of the Koran. an. Thus this study aims to reveal one of the figures of interpretation during the time of the companions, namely Ibn Abbas from various aspects, both in terms of the biography of Ibn Abbas's life, the pattern of interpretation, interpretation, characteristics of interpretation, and others. Tafsir Ibn Abbas covers various branches of Qur'anic science, one of which is the discussion of makki madani, this is also a reference for one of the mufassir of the archipelago, namely Sheikh Nawawi Bantani in writing his tafsir.